Use of environmental scans in health services delivery research: a scoping review - Shelley Doucet; Terri Kean; Patricia Charlton; Rima Azar; Daniel A Nagel; Leah Boulos; Alison Luke; Kim Mears; William Montelpare; Rebecca H Liu (BMJ Open, 2021)
Objective To examine the extent and nature of evidence on the use of the environmental scan (ES) in the health services delivery literature.Design Scoping review.Methods This scoping review followed the five-stage scoping review methodology outlined by Khalil et al. A Peer Review of Electronic Search Strategies was completed. Seven electronic databases and the grey literature were searched. Pairs of researchers independently performed two levels of screening and data extraction. Data were analysed using qualitative content and thematic analysis.Results Ninety-six studies were included in the scoping review. Researchers conducted ESs for many purposes, the most common being to examine the current state of programmes, services or policies. Recommendations were informed by ESs in 20% of studies. Most common data collection methods were literature review (71%), key informant or semistructured interviews (46%) and surveys (35%). Over half (53%) of the studies used a combination of passive (looking at information eg, literature, policies, guidelines) and active (looking for information eg, surveys, interviews) approaches to data collection. Person sources of data (eg, healthcare stakeholders, community representatives) and non-person sources of data (eg, documents, electronic databases, the web) were drawn on to a similar extent. The thematic analysis of the definitions/descriptions yielded several themes including instrument of discovery, knowledge synthesis, forward-looking and decision making. Research gaps identified included absence of a standard definition, inconsistencies in terminology and lack of guiding frameworks in the health services delivery context.Conclusion ESs were conducted to gather evidence and to help inform decision making on a range of policy and health services delivery issues across the continuum of care. Consistency in terminology, a consensus definition and more guidance on ES design may help provide structure for researchers and other stakeholders, and ultimately advance ES as a methodological approach. A working definition of ES in a health services delivery context is presented.